2018
DOI: 10.4187/respcare.05962
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High-Flow Nasal Oxygen in the Immunocompromised Critically Ill: A Systematic Review and Meta-Analysis

Abstract: BACKGROUND: High-flow nasal-cannula (HFNC) may be an oxygen modality useful for preventing invasive mechanical ventilation and mortality; however, its role in acute hypoxemic respiratory failure is not clearly defined. We sought to evaluate the impact of HFNC on mortality across immunocompromised subjects compared to alternative noninvasive oxygen therapies, namely conventional oxygen therapy and noninvasive ventilation (NIV). METHODS: We systematically searched the major databases to identify randomized, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
1
27
0
1
Order By: Relevance
“…The risk of bias will be assessed independently using the tools specified in the Cochrane Handbook for Systematic Reviews of Interventions for RCTs. [27][28][29][30] The following aspects will be assessed: This research will be done without patient involvement. Patients will not be invited to comment on the protocol design nor consulted to develop patient relevant outcomes.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of bias will be assessed independently using the tools specified in the Cochrane Handbook for Systematic Reviews of Interventions for RCTs. [27][28][29][30] The following aspects will be assessed: This research will be done without patient involvement. Patients will not be invited to comment on the protocol design nor consulted to develop patient relevant outcomes.…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…(8) Furthermore, although previous systematic reviews and meta-analyses have explored the effectiveness of HFNC in patients with AHRF, these studies have often pooled control group data as "any other strategy", failing to account for the important physiologic and clinical differences of these alternative interventions. (28)(29)(30) Network meta-analysis (NMA) is a strategy to summarize the evidence of clinical studies which include multiple treatments. 31…”
Section: Introductionmentioning
confidence: 99%
“…The risk of bias will be assessed independently using the tools specified in the Cochrane Handbook for Systematic Reviews of Interventions for RCTs. [27][28][29][30] The following aspects will be assessed:…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…(8) Furthermore, although previous systematic reviews and meta-analyses have explored the effectiveness of HFNC in patients with AHRF, these studies have often pooled control group data as "any other strategy", failing to account for the important physiologic and clinical differences of these alternative interventions. (28)(29)(30) Network meta-analysis (NMA) is a strategy to summarize the evidence of clinical studies which include multiple treatments. 31 The primary objective of this NMA is to assess the association between different non-invasive oxygenation strategies and all-cause mortality in adult patients with AHRF.…”
mentioning
confidence: 99%
“…16,17 Some systematic reviews and meta-analyses have reported that HFNC might decrease mortality and the use of invasive mechanical ventilation in immunocompromised subjects with ARF compared to other noninvasive oxygen strategies. 18,19 However, a recent meta-analysis, 20 which included a new large-scale trial, 21 found no benefit of HFNC over conventional oxygen therapy on mortality in immunocompromised subjects. These findings were consistent with another recent meta-analysis 22 that focused on a heterogeneous patient population, which included immunocompromised subjects.…”
Section: Introductionmentioning
confidence: 99%